Social Interaction and Corporate Culture in the Hybrid Work Era: A Qualitative Perspective - Sundari, Pipit; Khasanah, Aulia Sista Ayu Nur; Nugroho, Galih Satrio (Yayasan Gema Bina Nusantara, 2024)
This study aims to explore the impact of hybrid work systems on the dynamics of social interactions and the evolution of organizational culture in the context of multinational companies. We collected data through in-depth interviews with employees from various divisions and hierarchical levels in a multinational company that has implemented a hybrid work system, using a qualitative approach. The findings reveal that while hybrid work systems offer flexibility and boost productivity, they pose significant challenges due to the reduction in direct social interactions, which can negatively impact the company's sense of community and cultural identity. This study also revealed a tendency for organizational culture to fragment, leading to the formation of distinct subcultures between employees who work remotely and those who work in the office. Digital technology, while facilitating interaction in everyday communication, does not entirely replace the warmth and intimacy of face-to-face interactions. The implications of this study indicate the need for a more holistic strategy in supporting corporate culture in the era of hybrid work, including initiatives to strengthen the sense of community through more innovative and inclusive technology.